Analysis of Social Development Performance in the Education Sector Based on Net Enrollment Rate in Gorontalo City - Djunaida Kandow; Mohammad Zubair Hippy; Siti Rahmatia Machieu; Dian Rahayu Maku; Mustakim Mokoginta; Indriyati Lanangawa; Meilan Daud (International Journal of Education, Vocational and Social Science, 2026)
Social development in the education sector plays a strategic role in enhancing the quality of human resources, particularly in regions such as Gorontalo City, which is currently facing challenges in education access and participation. This study aims to analyze the performance of social development through the indicator of Net Enrollment Rate (NER) at the elementary, secondary, and tertiary education levels. The research employed a mixed-method approach with an explanatory sequential design, combining quantitative analysis of NER data from 2014–2024 and forecasting for 2025–2030 using regression, exponential smoothing, and ARIMA methods. This was complemented with in-depth interviews with relevant stakeholders. The findings reveal that the NER for primary schools is approaching its maximum value; however, NERs for junior high schools, senior high schools, and higher education still show disparities and fluctuations, driven by economic, social, and digital infrastructure limitations. The COVID-19 pandemic has further exacerbated these conditions. The study concludes that improvements in NER heavily rely on the continuity of affirmative policies and digital transformation in education. Therefore, it is recommended that local governments strengthen multi-sector collaboration, expand scholarship programs, and accelerate equitable education digitalization to promote equal access and sustainably increase educational participation at all levels.